Evolution of second trimester low implanted placenta to previa at term: a prospective cohort study - Shaaban, Omar M.; Ahmed, Hamdy A.; Ali, Mohammed K.; Abbas, Ahmed M.; Nasr, Ahmed; Makhlouf, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study is to identify the percentage of low implanted placenta (LIP) at second trimester of pregnancy and identify the risk factors of its persistence to placenta previa (PP) at term. Methods: Through a registered prospective cohort study conducted at tertiary hospital in Upper Egypt, authors screened all pregnant ladies comes to present facility for antenatal second trimester USG between 18-24 weeks gestation. All participants interviewed for detailed risk factors of placenta previa. Those diagnosed to have a LIP (≤1.5 cm from the internal os) had had TVS to confirm the exact distance between the lower edge of the placenta and the internal os. Serial USG had been done every 4 weeks up to delivery to measure the same distance. The primary outcome was the percentage of LIP at 18-24 weeks. Logistic regression analysis was performed to predict the risk factors for PP at term. Results: Through screening of 1000 pregnant lady, LIP had been identified in (52 cases) 5.2% of pregnant women between 18-24 weeks. This percentage dropped gradually to reach 1.3% at 36 weeks of gestation and at time of delivery. The logistic regression analysis demonstrated that the distance between the internal os and the lower edge of the placenta between 18-24 weeks was the single significant variable associated with PP at term (p<0.001, odds ratio 0.319, 95% CI 0.20-0.50). However, excluding the distance from the regression model demonstrated other risk factors as previous miscarriage, previous cesarean section (CS), and history of multiple pregnancies and history of previous PP. Conclusions: About 5.0% of pregnant women have LIP at the second trimester of pregnancy (18-24 weeks) and only 25.0 % of them remain placenta previa at term. A cut-off value of 10 mm between the internal os and the lower edge of the placenta is the most important predictor of development of PP.